Post medieval wreck in the bay of Sv. Nikola, island of Pag - Šelendić Taras, Ines; Taras, Dino (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The poster shows the results of a short investigation of a modern shipwreck in the bay of Sv. Nikola on the island of Pag. During the research the entire ship structure was excavated and subsequently documented, and a 3D model was created with the corresponding ortho image and drawing. The article provides basic data for the ship’s construction and descriptions of relevant parts of its structure. Radiocarbon analysis of wood fragments was also carried out dating the sampled element of the hull most probably to 18th century. Furthermore, an overview of possible modern types of ships to which the ship structure from the site would belong is presented.